Quasi‐Parallel Shock Reformation Seen by Magnetospheric Multiscale and Ion‐Kinetic Simulations. Issue 2 (25th January 2022) - Johlander, Andreas; Battarbee, Markus; Turc, Lucile; Ganse, Urs; Pfau‐Kempf, Yann; Grandin, Maxime; Suni, Jonas; Tarvus, Vertti; Bussov, Maarja; Zhou, Hongyang; Alho, Markku; Dubart, Maxime; et al.
Abstract: Shock waves in collisionless plasmas are among the most efficient particle accelerators in space. Shock reformation is a process important to plasma heating and acceleration, but direct observations of reformation at quasi‐parallel shocks have been lacking. Here, we investigate Earth's quasi‐parallel bow shock with observations by the four Magnetospheric Multiscale spacecraft. The multi‐spacecraft observations provide evidence of short large‐amplitude magnetic structures (SLAMS) causing reformation of the quasi‐parallel shock. We perform an ion‐kinetic Vlasiator simulation of the bow shock and show that SLAMS reforming the bow shock recreates the multi‐spacecraft measurements. This provides a method for identifying shock reformation in the future. Plain Language Summary: A shock wave forms when a supersonic flow encounters an obstacle. Shock waves can even form in the ionized plasma that inhabits most of the seemingly empty space in our solar system, galaxy, and the rest of the universe. One such a shock is found in front of Earth as the fast stream of plasma flowing from the Sun, known as the solar wind, encounters Earth's magnetic field. Under certain conditions, shock waves can become unsteady and evolve in time. Specifically, it is thought that a new shock can form in front of and replace the old shock in a process known as shock reformation. This process is important for how shock waves heat the plasma and can play a major role in how shocks accelerate particles. In this work, we use data from satellites that fly through Earth's shock and compare to a computer simulation of the shock wave. We find that a type of magnetic pulsation in front of the shock wave causes it to reform. The method of finding this reformation process presented here can also be used in the future to find shock reformation. Key Points: We present observations of the four MMS spacecraft crossing Earth's bow shock seemingly in the reverse order The observations, supported by an ion‐kinetic simulation, reveal that short‐large amplitude magnetic structures cause the shock to reform These multispacecraft signatures can be used in the future to identify shock reformation